Plasma zinc alpha2-glycoprotein levels correlate positively with frailty severity in female elders. Issue 35 (August 2016) - Lee, Ya-Ping; Chang, Chin-Hao; Liu, Heng-Hsiu; Chen, Chin-Ying; Chen, Ching-Yu; Hsu, Chih-Cheng; Chang, Ching-I; Lin, Yen-Ting; Lee, Chung-Sheng; Tsai, Jaw-Shiun
Abstract : Abstract: Frailty is a geriatric syndrome associated with adiposity. Zinc alpha2-glycoprotein (ZAG), a novel adipokine, is a modulator of body fat mass and positively correlates with age. This observational study aims to investigate the relationship between plasma ZAG levels and frailty in the elderly. We enrolled 189 elder participants from a hospital-based comprehensive geriatric assessment program in Taiwan from January 2007 to June 2008. The demographic data, body weight, body mass index, appendicular skeletal muscle mass index (ASMI), body fat mass percentage, metabolic and inflammatory parameters including plasma tumor-necrosis factor alpha, C-reactive protein and ZAG levels, were assessed. The frailty score was assessed by Fried Frailty Index. The mean age of all participants (91 [48.1%] men and 98 [51.9%] women) was 77.19 ± 6.12 years. Judged by the FFI score, 46 (24.34%) elders were robust, 106 (56.08%) were pre-frail, and 37 (19.58%) were frail. Older men showed greater ASMI and lower fat mass percentage in comparison to older women ( P < 0.0001). The log-transformed mean plasma ZAG (μg/mL) level of overall was 1.82 ± 0.11, and it was higher in men than in women (1.85 ± 0.12 vs 1.79 ± 0.1, P = 0.0006). Plasma ZAG levels were different among the robust, pre-frail and frail subgroups (1.78 ± 0.09, 1.83 ± 0.12, 1.83 ± 1.10, respectively, P = 0.028), and the differences were more significant in woman elders ( P = 0.005). Further multiple linear regression analysis showed plasma ZAG levels positively correlated with frailty severity in women ( P for trend = 0.0435). Plasma ZAG levels positively correlated with frailty severity in woman elders. The difference between sexes suggests certain sex-specific mechanisms may exist to affect the association between plasma ZAG levels and frailty.